Sociolinguistic Profile Research Importance of Social Factors in Language Teaching and Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the study of language in daily life, looking at how it operates in social relationships, the many media platforms we use, and the laws, customs, and regulations that surround language use. as linguistics. Additionally, it has been suggested that sociolinguistics may educate individuals about gender-neutral languages, multilingualism, regional dialects, and language politics in addition to drawing their interest in these concepts. In particular, language teachers should, above all, model for students the proper manner to observe other holidays and to value their own uniqueness as well as that of their peers. The role of an educator is to help learners analyze and draw lessons from their own sociocultural origins when the circumstances call for it. As a result, individuals are able to comprehend their own culture more fully, independent of its nuanced variances with their peers. Giving students the opportunity to present on their religious views, social mores, and cultural customs opens their minds to ideas outside of their comfort zones and gives them the opportunity to get feedback on the aforementioned procedures.